Sulfonohydrazide as a potential inhibitor of SARS-CoV-2 infection - Zoha Khan; Saba Farooq; Atia-tul-Wahab; Hana’a Iqbal; Farzana Naz; Thomas Iftner; Khalid M. Khan; Muhammad Yusuf; M. Iqbal Choudhary (Scientific Reports)
Abstract The COVID-19 pandemic caused immense mortality and morbidity reporting 704,753,890 cases worldwide. The repercussions of this pandemic are still being felt in the form of newly evolving variants and infections. The pandemic has pointed towards the need for the development of new and effective agents against SARS-CoV-2 infection. Sulfonohydrazides are a class of compounds with a wide range of therapeutic potential. The present study aims to identify the anti-SARS-CoV-2 potential of Sulfonohydrazide compounds. Twenty-five Sulfonohydrazides derivatives were evaluated for anti-viral potential via plaque reduction assay (PRA) and cytopathic effect (CPE) analysis in-vitro. Treatment point assay was employed for the strategic evaluation of antiviral compound at the particular stages of the SARS-CoV-2 life cycle. Gene expression analysis was also carried out, which was supported by immunofluorescence assays targeting the N and S proteins of SARS-CoV-2, alongside fold-change analysis, to identify a robust and multifaceted approach for the understanding of viral dynamics. Moreover, ligand-inhibitor interactions were assessed by in- silico studies. Compound 24 (4(E)-4-methyl-N’-(2,3,4-trihydroxybenzylidene)benzenesulfonohydrazide) was identified as the most potent molecule that inhibited SARS-CoV-2 infection (92.85 ± 3.57%) via PRA. The time point assay revealed that the effect of the compound might be at the entry point, which might be due to the down-regulation of the Spike (S) and Angiotensin-converting enzyme 2 (ACE-2) genes by the compound. The gene expression analysis of ORF1a/b by qRT-PCR indicated reduction in viral load after compound treatment, as indicated by a higher cycle threshold (Ct) value. Moreover, the compound 24 also downregulated the expression of S, RdRp, and ACE-2. Furthermore, the interaction of compound 24 with S, RdRp, and ACE-2 was predicted via molecular docking, which validated the interaction and possible anti-SARS-CoV-2 effect. Additionally, immunofluorescence staining analysis of spike and nucleocapsid proteins also showed downregulation in SARS-CoV-2 infected cells. Overall, the acquired data suggested that Sulfonohydrazide derivative 24 inhibits SARS-CoV-2 entry and replication.